The Limit Theories of Multivariate Extended Renewal Process - Kanišauskas, Vaidotas; Petrauskytė, Auksė; Petrauskytė-Caronkienė, Dovilė (Jaunųjų mokslininkų darbai, 2017)
The authors of this paper consider a multivariate extended renewal process. For the multivariate case the law of large numbers under the simplest conditions of validity was established.
Keywords: multivariate extended renewal process; law of large numbers